2019
DOI: 10.21608/jcvr.2019.34737
|View full text |Cite
|
Sign up to set email alerts
|

Development of PCR and Multiplex-PCR for Detection of Some Escherichia coli Virulence Genes from Bovine Neonates Diarrhea

Abstract: Colibacillosis is a fetal and serious problematic disease particularly in young calves during the first days of their life accompanied with high mortality losses. The aim of this study is to moleculary characterize Escherichia coli (E. coli) strains isolated from individual cases of neonatal calf diarrhea. Characteristic clinical symptoms as yellowish diarrhea with low colostrum feeding history was observed during samples collection. Rectal swabs were obtained from 50 healthy and 100 clinically infected diarrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…As it pertains to pathogenesis, E. coli utilizes various virulence factors to colonize and infect host cells. One factor is intimin (encoded by the eaeA gene), which plays an important role in the pathogenesis of attaching-and-effacing lesion, which facilitates the colonization of host tissues [50]. In our study, the eaeA gene was detected in four E. coli isolates (40%).…”
Section: Discussionmentioning
confidence: 59%
“…As it pertains to pathogenesis, E. coli utilizes various virulence factors to colonize and infect host cells. One factor is intimin (encoded by the eaeA gene), which plays an important role in the pathogenesis of attaching-and-effacing lesion, which facilitates the colonization of host tissues [50]. In our study, the eaeA gene was detected in four E. coli isolates (40%).…”
Section: Discussionmentioning
confidence: 59%
“…Other reports showed that E. coli strains isolated from cattle in Lithuania, China, and Egypt could harbor those pathogenic genes, including fuyA, traT, and tsh. These strains were considered the main cause of sepsis and mastitis in humans and cattle (Fathy et al 2019;Kirtikliene et al 2022;Shoaib et al 2023). Furthermore, Bacciu et al (2004) indicated that an intergeneric transfer of virulence genes via an insertion sequence from E. coli to other pathogens and horizontal transfer of virulence factors between bacterial genera occurred in nature.…”
Section: Discussionmentioning
confidence: 99%
“…These genes were considered the main cause of animal mastitis and transmitted to humans through contaminated milk, meat, surface water, and agricultural crops. Fathy et al (2019) also reported that gene tsh was detected from E. coli strains isolated from diarrhea newborn calves in Egypt. Thus, it was revealed that those pathogenic genes could cause diseases in cattle and humans.…”
Section: Introductionmentioning
confidence: 94%